2017
DOI: 10.1177/1934578x1701200204
|View full text |Cite
|
Sign up to set email alerts
|

Crataegus orientalis Leaves and Berries: Phenolic Profiles, Antioxidant and Anti-inflammatory Activity

Abstract: The present study was designed to define the phenolic content, antioxidant and anti-inflammatory activity of Crateagus orientalis Pall. ex M. Bieb., traditionally used by local people in southern parts of F.Y.R. Macedonia. The presence and content of 7 phenolics in ethanolic extracts of leaves and berries were studied using HPLC-DAD, where the most dominant compounds were hyperoside, isoquercitrin and chlorogenic acid. The leaf extract was more effective as a DPPH radical scavenger (IC 50 = 29.7 µg/g) than the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 26 publications
2
8
1
Order By: Relevance
“…However, this previous study reported a total phenolic content of 33.88 ± 0.28 mg GAE/g d.w. in other C. monogyna leaf extract obtained at other locations, which was 56.6% lower than that obtained in the present study [25]. Therefore, data show significant differences in total phenolic content of hawthorn due to several factors such as natural habitat, genotype, growth stage, extraction procedure and method for determination of total phenolics [24]. Figure 1A shows the maximum TPC in the range of 45-75% acetone/water and 55-75 min, whereas in Figure 1B its maximum concentration is observed at 50-70% acetone/water and 700-1200 solvent-to-solid ratio (v/w), and in Figure 1C its maximum value shows at 50-70 min and 700-1200 solvent-to-solid ratio (v/w).…”
Section: Optimization Of Ultrasonic-assisted Extractioncontrasting
confidence: 75%
See 1 more Smart Citation
“…However, this previous study reported a total phenolic content of 33.88 ± 0.28 mg GAE/g d.w. in other C. monogyna leaf extract obtained at other locations, which was 56.6% lower than that obtained in the present study [25]. Therefore, data show significant differences in total phenolic content of hawthorn due to several factors such as natural habitat, genotype, growth stage, extraction procedure and method for determination of total phenolics [24]. Figure 1A shows the maximum TPC in the range of 45-75% acetone/water and 55-75 min, whereas in Figure 1B its maximum concentration is observed at 50-70% acetone/water and 700-1200 solvent-to-solid ratio (v/w), and in Figure 1C its maximum value shows at 50-70 min and 700-1200 solvent-to-solid ratio (v/w).…”
Section: Optimization Of Ultrasonic-assisted Extractioncontrasting
confidence: 75%
“…The total phenolic content obtained in C. monogyna leaf extract at optimum conditions was in the magnitude order than a previous study in an extract of C. orientalis leaves, which was 94.2 mg GAE/g d.w. Nevertheless, this previous study reported an extraction in a Soxhlet apparatus for 72 h with 96% ethanol [24]. Therefore, it has been shown that ultrasonic-assisted extraction is more efficient than conventional extraction techniques due to requiring lower extraction times to obtain a similar phenolic recovery from Crataegus leaves.…”
Section: Optimization Of Ultrasonic-assisted Extractionmentioning
confidence: 99%
“…In addition, Que reduces T cell proliferation by blocking IL-12-induced tyrosine phosphorylation of JAK2, TYK2, STAT3, and STAT4 (Muthian and Bright, 2004;Nabavi et al, 2012). In inflammation, Que inhibits the enzymes COX and lipoxygenase (Lee and Min, 2013;Savikin et al, 2017). In the RAW 264.7 cell line, Que was also shown to counteract LPSinduced inflammation by phosphorylation of tyrosine phosphatidylinositol-3-kinase (PI3K)-p85 and complex formation of toll-like receptor 4 (TLR4)/MyD88/PI3K (Endale et al, 2013).…”
Section: Quercetinmentioning
confidence: 99%
“…Flavonoid, epicatechin, chlorogenic acid (Sargin, 2015;Savikin et al, 2017) Leaf, Fruit Decoction Internal/drink one glass 2-3 times a day for 3-5 weeks Nephralgia, Kidney gravel (Sargin et al, 2015) Leaf, Fruit, Seed Raw, Mash, Decoction, Infusion…”
Section: Infusion Decoction Rawmentioning
confidence: 99%